Quantitative assessment of soil CO2 concentration and stable carbon isotope for leakage detection at geological carbon sequestration sites. Issue 4 (28th April 2017) - Yang, Changbing; Jamison, Keith; Xue, Lianqing; Dai, Zhenxue; D. Hovorka, Susan; Fredin, Leif; H. Treviño, Ramón
Abstract: This study presents a quantitative method to evaluate CO2 concentration ([CO2 ]) and stable carbon isotope ratio (δ 13 C) as indicators for leakage detection at a geological carbon sequestration site by combining use of field release tests and a numerical modeling approach. A numerical model was developed to simulate CO2 dynamics by considering diffusion, dissolution in soil water, and soil respiration. The numerical model fits the background dynamics of [CO2 ] (360 to 550 ppm) and δ 13 C (‐16‰ to ‐6‰) well and reproduces fairly the overall trend observed during the CO2 release test. The model was further applied to assess detection probability (DP) of [CO2 ] and δ 13 C for leakage detection in terms of various factors, such as CO2 leakage rate, background variations, δ 13 C of the CO2 leaked, and the threshold value of signal‐to‐noise ratio. Modeling results suggest that δ 13 C may have a higher DP than [CO2 ]. This study also shows that DP of δ 13 C for the IEA Weyburn project is close to 0, implying δ 13 C is inappropriate to be an indicator for CO2 leakage at the site. The quantitative method developed can also be used to design a monitoring plan or strategy in a near‐surface environment for geological carbon sequestration. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd.